2016
DOI: 10.1108/oir-05-2015-0155
|View full text |Cite
|
Sign up to set email alerts
|

Online sustainability information in European local governments

Abstract: Purpose – The purpose of this paper is to propose an analytical model that shows causal relationships between the amount and nature of information on strategies and the governance of city councils, as well as the contents of different dimensions of sustainability that are disclosed on the websites of local governments in big European cities. This model could reveal if the information is disseminated in a homogeneous and coordinated way and could improve the quality of the information, its coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…This research confirms that reforms carried out within public administrations are influenced by their cultural, political and legal context [2,5,7,17,[30][31][32]49]. However, some researchers have performed comparative analyses of local governments in different countries, and have reported that the explanatory variables of transparency about governmental sustainability (where social and environmental aspects were included) may depend on the administrative culture prevailing in the country (Anglo-Saxon, Southern European or Continental) [2,35,43,50].…”
Section: Prior Research On Local Government Transparency On Sustainabsupporting
confidence: 64%
See 2 more Smart Citations
“…This research confirms that reforms carried out within public administrations are influenced by their cultural, political and legal context [2,5,7,17,[30][31][32]49]. However, some researchers have performed comparative analyses of local governments in different countries, and have reported that the explanatory variables of transparency about governmental sustainability (where social and environmental aspects were included) may depend on the administrative culture prevailing in the country (Anglo-Saxon, Southern European or Continental) [2,35,43,50].…”
Section: Prior Research On Local Government Transparency On Sustainabsupporting
confidence: 64%
“…Reflecting growing demands by stakeholders for information, various international organizations have called on governments to publish information on their actions in the field of sustainability [9][10][11]13,41]. In response to these pressures, many government agencies now include references to social and environmental questions in their annual reports [2,4,31,42,43]. In this sense, sustainability, as defined by IFAC [17], combines the economic, social and environmental perspective.…”
Section: Prior Research On Local Government Transparency On Sustainabmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for data collection consisted of: first, two researchers sought the information within websites separately; second, the information indicated was pooled; in case of divergence, a value of 1 was selected, since it meant one of the two researchers had found the variable on the web. This process of data collection has been validated in previous research [58].…”
Section: Methodsmentioning
confidence: 99%
“…The results of this paper found that GP practices affected firm performance and technical aspects. Table A7 (see Appendix A) mentioned the analysis of 28 studies [265][266][267][268][269][270][271][272][273][274][275][276][277][278][279][280][281][282][283] regarding green and sustainable operation management based on the author(s) names, year of publication scope and sample of study, area of study, number of sample, respondents, related theory, variables, study purpose, gap and research problem and results and outcome.…”
Section: Breakdown Of Articles Based On Other Green and Sustainable Omentioning
confidence: 99%